Mosque Branding Theory: From Distinction to Innovation - Bambang Sukma Wijaya (Jobmark: Journal of Branding and Marketing Communication, 2024)
Mosques have evolved into more than just spiritual magnets; they are also engines of cultural and social inspiration. Amid the decline in youth religiosity, eroded by the allure of hedonism and the glitz of technology, mosques are shaping new values ​​that transcend their primary function as places of worship. Mosques serve as channels for new identities, new meanings, and new comforts that not only support spiritual achievement but also foster a unique sense of pride. This article discusses a new approach that views mosques as brands with the potential to leave a lasting imprint on people's minds and hearts. Theoretically, five aspects shape a mosque brand. First, Mosque Brand Distinction, which emphasizes physical uniqueness, figures, history, distinctive stories, and prominent programs. Second, Mosque Brand Communication, which manages messages, media, narratives, images, and information amplification. Third, the Mosque Brand Community builds engagement, participation, trust, loyalty, and advocacy among congregants. Fourth, Mosque Brand Outreach, which expands reach through religious services, social initiatives, learning spaces, cultural inspiration, and humanitarian light. Fifth, Mosque Brand Innovation, encompassing innovations in services, communications, programs, approaches, and sociocultural encryption.